Oral Administration of Alkylglycerols Differentially Modulates High-Fat Diet-Induced Obesity and Insulin Resistance in Mice. (20th June 2013) - Zhang, Mingshun; Sun, Shuna; Tang, Ning; Cai, Wei; Qian, Linxi
Abstract : Alkylglycerols (AKGs) from shark liver oil (SLO) were demonstrated to have strong potency to stimulate immune response. However, no study has been conducted on the effects of AKGs on diet-induced obesity and metabolic inflammatory disorder. The purpose of the present study was to investigate the effect of two AKGs isoforms on obesity and insulin resistance in mice fed high-fat (HF) diet. Forty-eight C57BL/6 mice were divided into normal, HF, H F + 20 mg/kg selachyl alcohol (SA), H F + 200 mg/kg SA, H F + 20 mg/kg batyl alcohol (BA), and H F + 200 mg/kg BA groups. Body weight, fasting glucose, lipids, insulin and leptin levels, serum IL-1 β, and TNF- α levels were compared among different groups. Our results showed that high-dose SA decreased body weight, serum triglyceride, cholesterol, fasting glucose level, insulin level, and serum leptin level of the HF fed mice, while high-dose BA increased fasting insulin level of the HF fed mice. Pretreatment of primary adipocytes with 10 μ M SA or BA differentially modulates LPS-mediated MAPK and NF- κ B signaling. Our study demonstrated that oral administration of AKGs has differential effects on HF-induced obesity and metabolic inflammatory disorder in mice.